Features of the use of physical training in correctional and educational work with children who are marked deprivation of view - V. I. Melnyck; G. A. Iedinak; S. P. Demchuk (Kazimierz Wielki University, 2016)
Information reviewed scientific literature on the organization and peculiarities of physical education and its implementation in the education of children with deprivation of view in a specialized boarding school. Physical activity of children with deprivation was of view established during each school day is below the physiological norm. One of the reasons for this situation is not rational organization of mass and group sports and recreational activities, as well as low efficiency of their content. The result of it is the low values of the physical condition, including describing one of the components of the state, such as physical health. Thus, mass and group sports and recreational activities are effective means of corrective and educational work in a specialized school for children with deprivation of view. However, at present the actual problem is improving the organization, formation and implementation of the content of mass and group sports and recreational activities for successful adaptation of children in society livelihoods.